2013
DOI: 10.1111/wej.12058
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing selection of drinking water technologies for urban informal settlements in Kampala

Abstract: Access to drinking water in urban informal settlements of developing countries still remains a challenge for the poor and depends on technology selected. This paper determines the score on criteria used for technology selection by two major stakeholders in the water service delivery chain, the users and the utility. The criteria are: affordability to connect, affordability of consumption, method of payment, ease of operation, ease of spare parts acquisition, access distance, access time, generating sufficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Considering risk perception as well as the complexity of health challenges related to water and sanitationincluding economic, social, cultural, and political factors could lead to improved risk management. In particular, Bwaise is a settlement with a transient population, as pointed out in previous studies , and evidenced by surveys from this study, indicating that approximately 52% of respondents had lived there for 10 years or less. Additionally, the majority of surveys indicated that women are typically responsible for both water collection (78% of respondents) and treatment (96% of respondents).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Considering risk perception as well as the complexity of health challenges related to water and sanitationincluding economic, social, cultural, and political factors could lead to improved risk management. In particular, Bwaise is a settlement with a transient population, as pointed out in previous studies , and evidenced by surveys from this study, indicating that approximately 52% of respondents had lived there for 10 years or less. Additionally, the majority of surveys indicated that women are typically responsible for both water collection (78% of respondents) and treatment (96% of respondents).…”
Section: Resultssupporting
confidence: 73%
“…To this end, this study explores opportunities to improve the utility of QMRA for decision-making in resource-limited settings by focusing on the application of QMRA to WaSH in Bwaise, an informal settlement in Kampala, Uganda, as a case study that can be replicated elsewhere. Challenges surrounding water (e.g., affordability and travel distances), sanitation (e.g., difficulty in latrine emptying), and hygiene in Bwaise have been highlighted in previous studies. In particular, Katukiza and colleagues performed QMRA to characterize health risks from Escherichia coli, Salmonella, rotavirus, and adenovirus in drinking water, gray water, surface water, and soil . The present study builds on this previous work by including an additional exposure pathway (hand-to-mouth contact) and integrating comprehensive uncertainty and sensitivity analyses across the QMRA framework.…”
Section: Introductionmentioning
confidence: 87%
“…There is moderate quantitative evidence and strong qualitative evidence that vulnerable people are at risk of discrimination or physical, sexual and psychological abuse while they collect water ( tables 3 and 4 ). The studies in this review provide rich qualitative evidence in good, 49 51 54 55 57 fair 31 47 48 and poor quality studies 32 50 58 from 31 countries, and good, 30 fair 31 37 or poor 31 32 35 41 42 quantitative evidence from 6 countries ( table 9 ). People may be vulnerable because of age, gender, disability, health status or ethnicity.…”
Section: Resultsmentioning
confidence: 91%
“…The water source of The First Water Supply and Drainage Company is groundwater. The Second Water Supply and Drainage Company's water source used to be deep underground well water [6], but it has gradually changed to surface water. Shanshan's rural drinking water is primarily a centralized water supply.…”
Section: Analysis Of the Status Quomentioning
confidence: 99%